Delineation of Taxonomic Species within Complex of Species: Aeromonas media and Related Species as a Test Case - Talagrand-Reboul, Emilie; Roger, Frédéric; Kimper, Jean-Luc; Colston, Sophie M.; Graf, Joerg; Latif-Eugenín, Fadua; Figueras, Maria José; Petit, Fabienne; Marchandin, Hélène; Jumas-Bilak, Estelle; Lamy, Brigitte (Frontiers in Microbiology, 2017)
Aeromonas media is an opportunistic pathogen for human and animals mainly found in aquatic habitats and which has been noted for significant genomic and phenotypic heterogeneities. We aimed to better understand the population structure and diversity of strains currently affiliated to A. media and the related species A. rivipollensis. Forty-one strains were included in a population study integrating, multilocus genetics, phylogenetics, comparative genomics, as well as phenotypics, lifestyle and evolutionary features. Sixteen gene-based multilocus phylogeny delineated three clades. Clades corresponded to different genomic groups or genomospecies defined by phylogenomic metrics ANI (average nucleotide identity) and isDDH (in silico DNA-DNA hybridization) on 14 whole genome sequences. DL-lactate utilization, cefoxitin susceptibility, nucleotide signatures, ribosomal multi-operon diversity and differences in relative effect of recombination and mutation (i.e. in evolution mode) distinguished the two species Aeromonas media and Aeromonas rivipollensis. The description of these two species was emended accordingly. The genome metrics and comparative genomics suggested that a third clade is a distinct genomospecies. Beside the species delineation, genetic and genomic data analysis provided a more comprehensive knowledge of the cladogenesis determinants at the root and inside A. media species complex among aeromonads. Particular lifestyles and phenotypes as well as major differences in evolution modes may represent putative factors associated with lineage emergence and speciation within the A. media complex. Finally, the integrative and populational approach presented in this study is considered broadly in order to conciliate the delineation of taxonomic species and the population structure in bacterial genera organized in species complexes.